QARAQALPAQ TILINDE AQ HÁM QARA REŃLERINIŃ METAFORIZACIYASÍ - Djumamuratova, G. (SCIENCE and SOCIETY, 2025)
This article examines the various meanings of words denoting white and black colors in the Karakalpak language. It was also analyzed that white and black express different meanings in literary texts through the methodology of metaphorization.